PENATALAKSANAAN FISIOTERAPI PADA KASUS HNP DENGAN MODALITAS SHORTWAVE DIATERMY,TRAKSI LUMBAL DAN MC. KENZIE EXERCISE DI RSUD. Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Dwi Susilo Ady Nugroho; Andung Maheswara (LPPM Universitas Pekalongan, 2013)
In patients with HNP (Hernia Nucleus Pulposus) will usually arise low back pain that radiates to the lower leg area even up to the end of the toes and also characterized by severe pain when the patient straining or sneezing. Given the pain, then there will be muscle spasm around the vertebrae and limited motion in the lumbar spine (flexion, extension,). Issues arising from this, will affect the activities of daily life can’t work according to their field and can’t enjoy leisure time due to pain breaks. For effective and efficient handling performed an inspection method nyri with VDS (Visual Descriptive Scale), muscle strength checks MMT (Manual Muscle Testing) examination joints with limitation of motion of LGS (Mid line) Examination of the functional activity Owestry scale. As for the goal to be achieved in reducing muscle spasm pain and, increase muscle strength, increase range of motion, and improve the patient's functional activities for daily life - today. Most patients will improve HNP in 6 weeks with conservative therapy. Small proportion will develop into chronic despite terapeutik, in patients in surgery 90% will be improved, especially leg pain, but the likelihood of recurrence is 50% and can be at the same level or different discs.Key Word : HNP, Intervensi SWD, Traksi Lumbal, and Mc. Kenzie exercise.